Strategy of The Directorate of Narcotics Interdiction of The DJBC To Supervise The International Narcotics Smuggling To Indonesia - Aldila Kun Satriya (Publikasi Indonesia, 2023)
The Directorate General of Customs and Excise (DJBC) as the